Rates of visual field change and functional progression in glaucoma following trabecular microbypass implantation of iStent technologies: a meta-analysis - Kevin Gillmann; Dana M Hornbeak (BMJ Open Ophthalmology)
Background/aim While intraocular pressure (IOP) remains the only modifiable risk factor for glaucoma progression, the ultimate goal of glaucoma management is to preserve patients’ functional vision and quality of life. To this end, minimally invasive glaucoma surgeries (MIGSs) aim to reduce IOP with minimal eye trauma. Commonly used MIGS devices include iStent technologies, which have well-documented IOP-reducing potential and favourable safety profiles. However, no study concluded on their effect on the rates of visual field (VF) changes. The aim of this meta-analysis is to determine the long-term effect of iStent technology implantation on glaucoma functional progression.Methods Electronic medical literature databases were searched to identify studies reporting on iStent technologies. Reports with follow-up durations <12 months, retention rates <75% and missing VF data were excluded. Fifteen studies reporting on 1115 eyes were identified. The overall weighted mean VF mean deviation (MD) progression, IOP reduction and follow-up duration were calculated.Results Weighted mean IOP at baseline was 19.0±3.1 mm Hg. At the end of a 37.9-month mean follow-up (range 12–96 months), a weighted mean 26.6% IOP reduction was achieved (range 15.2%–42.3%). Over the same duration, the weighted mean VF MD progression rate was −0.02±0.34 dBs/year, from a mean baseline of −5.76±5.68 dBs.Conclusion In this review, which examines functional stability of 1115 eyes, iStent technologies achieved a mean rate of progression of −0.024 dBs/year with serial standard automated perimetry, which is similar to that reported in non-glaucomatous eyes and slower than that reported in medically treated glaucoma.